126. evaluation of Addition of Outpatient Parenteral Antimicrobial Therapy and Orthopedic ID Resources to Transitions-of-care Outcomes. (31st December 2020) - Young, Brett; Bergman, Scott; Van Schooneveld, Trevor C; Cortes-Penfield, Nicolas W; Alexander, Bryan
Abstract: Background: Our large academic medical center initiated both an Outpatient Parenteral Antimicrobial Therapy (OPAT) program supported by an infectious disease trained pharmacist, along with an Orthopedic Infectious Disease (OID) consult service to assist in caring for these specialized populations. We measured the impact of these services. Methods: Patients discharged on parenteral antimicrobial therapy were divided into two groups. The pre-OPAT cohort included all patient receiving OPAT from 4/1/18 - 10/31/18; the post-OPAT cohort included all patients who received OPAT from 4/1/19 - 10/31/19 with OPAT consult (Fig 1). The OID consult service began in September 2018 prior to initiation of the OPAT program. The primary outcome was 30-day hospital readmission. Secondary outcomes included: length of stay (LOS), 90-day readmission, clinical outcomes, and identification of predictors of hospital readmission. Clinical outcomes included: time from final OR visit to discharge for OID patients and optimal treatment (cefazolin, oxacillin, or nafcillin) for MSSA. Results: Introduction of these programs was associated with a reduction in all-cause 30-day readmission from 39.3% to 22.9%, and a reduction in 30-day readmission for patients on-treatment from 24.6% to 15.6% (p< 0.01 for both). No difference was seen in hospital LOS (8 days in each cohort). In a subgroup analysis (Fig 2), OID patients in the post-OPAT cohort saw a median reduction of 2 days (7 days to 5 days, p=0.002) in time from final OR visit to discharge. Use of optimal treatments for MSSA increased in the post-OPAT cohort compared to pre-OPAT (65.2% to 80.9%; p=0.06). The 90-day hospital readmission rate were higher in the post-OPAT cohort among patients who lived in metro-area zip codes (p=0.03). Having an established primary care physician was associated with lower 90-day hospital readmission in both the pre-and post-OPAT cohorts (p=0.05 and 0.01, respectively). Conclusion: Thirty-day readmission rates among patients discharged on OPAT significantly lowered following initiation of a combination of both a pharmacist-led OPAT program and OID consult service. OPAT and OID programs accrue additional efficiencies and clinical benefits to both patients and hospitals, which can be further evaluated and used to justify such service additions. Disclosures: All Authors : No reported disclosures